2006
DOI: 10.1111/j.1445-2197.2006.03786.x
|View full text |Cite
|
Sign up to set email alerts
|

No Rest for the Wounded: Early Ambulation After Hip Surgery Accelerates Recovery

Abstract: EA after hip fracture surgery accelerates functional recovery and is associated with more discharges directly home and less to high-level care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 14 publications
7
179
0
2
Order By: Relevance
“…However, this affected clinical practice and resources (Tsauo et al, 2005). Oldmeadow et al (2006) compared the effects of early mobilisation against delayed ambulation post-operatively. Early ambulation promoted functional recovery with an increased discharge rate to the home environment and reduced the need for higher level of care.…”
Section: Professional Focusmentioning
confidence: 99%
“…However, this affected clinical practice and resources (Tsauo et al, 2005). Oldmeadow et al (2006) compared the effects of early mobilisation against delayed ambulation post-operatively. Early ambulation promoted functional recovery with an increased discharge rate to the home environment and reduced the need for higher level of care.…”
Section: Professional Focusmentioning
confidence: 99%
“…The review included a total of 22,443 patients and 97 health professionals. In total, 6282 (range 90-401) patients participated in RCTs, 12,69,78,80,87,[128][129][130]197,199 276 (range 24-95) patients participated in quasi-RCTs, 83,[131][132][133] 116 (range 20-30) patients participated in non-RCTs, 79,[134][135][136][137] 3044 (range 1-919) patients participated in historical cohort studies, 13,[157][158][159][160][161][162][163][164][165]170,173,178 7136 (range 18-946) patients participated in concurrent cohort studies, 81,[138][139][140][141][142][143][144][145][146][147][148][149][150][151][152]169,177,179,…”
Section: Summary Of Participant Characteristicsmentioning
confidence: 99%
“…185 Eight studies included patients aged ≥ 50 years; 87,98,103,118,173,187,188,192 18 studies included patients aged ≥ 60 years; 12,89,96,104,114,117,119,122,132,133,149,154,164,[193][194][195][196][197] 19 studies included patients aged ≥ 70 years; 69,72,79,88,106,108,110,111,116,120,131,136,143,148,150,161,180,183,184 and seven studies included patients aged ≥ 80 years. 13,81,123,134,137,152,178 The age of the included participants could not be determined from the study reports for four studies.…”
Section: A Community-based Multidisciplinary Rehabilitation Package Fmentioning
confidence: 99%
“…30 Early mobilization within 2 days after surgery to repair a hip fracture has been demonstrated to improve patient mobility and increase the likelihood of patients being discharged directly home. 31 However, a Cochrane review assessing mobilization strategies following hip fracture surgery in adults concluded that the evidence base for effective rehabilitation strategies is limited, with no one mobilization strategy emerging as the preferred treatment. 32 It has been suggested that the success of hospital-based rehabilitation programmes depends upon the co-ordination of multidisciplinary teams consisting of experts in a variety of medical, allied-health, social and educational fields.…”
Section: Rehabilitation Programmesmentioning
confidence: 99%